Viscount Scudamore's ‘Laudianism’: the Religious Practices of the First Viscount Scudamore - Atherton, Ian (The historical journal, 1991)
Viscount Scudamore had three great passions: God, cider and cattle, in that order. He was remembered for cultivating cider apples, breeding cattle, his learning, and most of all for his piety, rebuilding one church, endowing others and aiding distressed divines during the interregnum. Many commended his erudition. He stood on the fringes of that republic of letters which revolved around Mersenne, a friend of the philosophers Hobbes, DuBosc and Grotius, and known to Samuel Hartlib who considered him ‘a great schollar and studying hard continually’. In particular he was a great reader of theology. William Laud had to warn him to ‘Booke it not to much’ while William Higford advised his grandson to ask the viscount, ‘a great lover of learning and very learned’, to guide his own study. The viscount recommended Jeremy Taylor's Holy living and Holy dying to his son, whilst consulting with Laud and Henry Hammond for his own reading. Hammond directed him to Augustine, Aquinas, Peter Lombard, Suarez and Grotius; clearly he was no beginner. In the early eighteenth century Matthew Gibson, Scudamore's first biographer, was astonished at the amount oftheological notes amongst the first viscount's papers. These, however, have all but disappeared. DespiteScudamore's famed ‘affection to Divine knowledge…[and] good proficiencie in it’, it is no longer possible to construct a system of divinity for the viscount, if he did ever work out his theological position comprehensively; perhaps like his friend William Laud he preferred to leave off the deep points of divinity.